IMPLEMENTASI DANA DESA DAN PERGESERAN POLITIK BIROKRASI - Wahyu Kuncoro (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
The government rolled out the implementation of village funds, the contra pro erupted colored the rural dynamics. Implementation of Law No. 6/2014 became a milestone in the history of rural governance in Indonesia. Many hopes depend on village fund management. The issue of pulling behind village funds, ministries that must be responsible, recruitment of village assistants, village staff HR, program operations, reporting and transparency for complicated issues, the central government must find the right formula. On the other hand, village funds are the hope of the village community and the progress of rural development, its presence like a windfall. The magnitude of the figures disbursed in each village is also different from attracting interest at the parliamentary level. The tendency to re-conflict the role of the bureaucracy, where political pragmatism is very prominent among village bureaucrats. Conflicts of interest in the choice of staff to accompany the village, for example, are one of the problems that arise. Keywords: village funds, bureaucracy, implementation of Law No.6 / 2014, public services